Seasonal dynamics of gonads maturity and indices of body condition for walleye pollock Theragra chalcogramma in the northern part of the Okhotsk Sea - Alexander I. Varkentin (Известия ТИНРО)
Seasonal dynamics of gonad maturity and body condition indices (liver weight, hepato-somatic index, weight-size ratio) is analyzed for walleye pollock in the northern Okhotsk Sea. Its spawning season is rather long both for the whole population and any spawning ground, e.g. at West Kamchatka the fish with melting gonads is observed from December to September and probably later, but the mass spawning continues about one month - in March-April, on average. After the spawning, a new annual biological cycle begins from the period of gonad recuperation (stages of gonad maturity VI and VI-II) that continues 2-3 months followed by the period of gonad maturation from the stage III to the next spawning. The portion of the pollock females and males with the stage III is the highest in August-September, and with the stage IV - in March, before the mass spawning. In the northern Okhotsk Sea, the dynamics of maturing is similar, with the lag of 2-3 weeks. However, the gonad maturing depends on thermal conditions: they develop faster in «warm» years than in «cold» ones. Besides, big fish begin to spawn earlier than small ones spawning in the first time. Males usually stay on the spawning grounds longer than females. Body condition of walleye pollock is influenced by the process of gonad maturation. Energy potential of its individuals forms until August-September, and begins to decrease when gonads transform from the stage III to the stage IV. Later the indices of body condition continue to decrease till spawning in March-April, and melting individuals and postspawners have the lowest values. After the spawning, the indices begin to grow again because of active feeding.